Optimal allocation of scarce resources in the construction industry - Sheikh, Naveed Athar; Scott, David; Jearkjirm, Vithool; Usami, Tsutomu; The Royal Irrigation Department (RID) of Thailand and the International Labour Office (ILO), Thailand (Bangkok : Asian Institute of Technology, 1977)
The purpose of this study is to investigate the feasibility of sub stituting labour-intensive methods for the capital-intensive ones in the construction industry. The scope of the study is confined to earthworks only, because these offer a great potential for substantial substitution; The concepts of networks and the critical path analysis are used to investi gate the feasibility of using an intermediate approach, where the jobs which are critical are executed by mechanical means and the ones which are non critical are executed by labour-intensive means. A project of the Royal Irrigation Department (RID) of Thailand is used to illustrate the working of the model. Results of this study have indi cated that totally labour-intensive methods of construction are competitive cost-wise but result in an increased duration of the project. The interme diate approach which combines the use of capital-intensive methods with the labour-intensive ones, is found to be the most suitable in terms of cost, time, employment generation and resource optimization.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Underdeveloped areas -- Construction industry